Islam dan Logika Menurut Pemikiran Abu Hamid Al-Ghazali - Muhammad Nur (Al-Ulum, 2011)
This article aims to describe the Abu Hamid Muhammad Al-Ghazali’s Logic that includes: (1) to describe objectively the Abu Hamid Muhammad Al-Ghazali’s Logic of science essense, science classification, and urgency of logic in science development; (2) to describe the Abu Hamid Muhammad Al-Ghazali’s logic as a tool to get valid knowledge. (3) to describe philosophical thingking af Al-Ghazali in logical aspect. It includes many forms of thingking such as deduction, induction and analogy. It is also in connection with inference process (the final process in logic); (4) to study critically and heuristically relevance of Al-Ghazali’s logic to science development especially in Islamic science.